Controlled-release fertilizer affects leaf nitrogen allocation and photosynthesis to improve nitrogen use efficiency and yield in the sunflower field - Ren, Wenhao; Li, Xianyue; Liu, Tingxi; Chen, Ning; Xin, Maoxin; Qi, Qian; Liu, Bin (Frontiers in Plant Science, 2025)
IntroductionNitrogen (N) can significantly affect the photosynthetic rate (Pn) of plants. Under traditional nitrogen fertilization (TNF) or inappropriate nitrogen application, leaf N is often redistributed to support the seed protein accumulation rather than the photosynthesis in the later stages of crop growth. Controlled-release fertilizers (CRF) have been reported to effectively reduce the nitrogen loss by matching the release pattern with crop N demand, thus increasing the yield. However, the changes in N allocation to enhance the photosynthesis under CRF have rarely been addressed.MethodsA two-year field experiment was conducted in the Hetao Irrigation District, Inner Mongolia, China from 2019 to 2020 to evaluate the effects of different fertilization strategies on soil NO3-N concentration, leaf nitrogen content, photosynthetic characteristics, yield, and nitrogen use efficiency (NUE) in sunflowers. The treatments included the CRF application rates of 135, 225, and 315 kg/ha (CRF135, CRF225, and CRF315), and that of TNF at 225 kg/ha (TNF225).ResultsThe results demonstrated that applying CRF at an appropriate rate maintained a high level of photosynthetic nitrogen content in the leaves during the later growth stages. This rate ensured a suitable soil NO3-N concentration (SNC), resulting in a 76.10% higher proportion of photosynthetic nitrogen (Npsn) than TNF at the same rate, significantly enhancing the photosynthetic nitrogen efficiency (PNUE) and highlighting the crucial role of nitrogen management in improving the crop productivity and NUE. Additionally, at CRF225, the net photosynthesis (Pn), stomatal conductance (Gs), and intercellular CO2 concentration (Ci) at maturity increased by 32.80%, 96.16%, and 13.56%, respectively, compared to TNF, leading to an 11.84% improvement in yield and a 9.70% increase in NUE.DiscussionThe correlation analysis confirmed a strong positive relationship between leaf N redistribution and photosynthetic efficiency, demonstrating the potential of CRF to improve the photosynthetic efficiency, optimize the N management, and promote the environmental sustainability in sunflower cultivation.